نفقة الوالدين: دراسة فقهية مقارنة في الفقه الإسلامي وقانون الأحوال الشخصية الأردني - العمري، سامرة محمد حامد; الشرع، صفية علي أحمد (الجامعة الأردنية - عمادة البحث العلمي, 2019)
This research deals with one of the most important topics of the expenses of relatives in Islamic jurisprudence, in which the rich relative financially helps poor relatives. The research specifically explains the issue of parental expenses and its principles with the specific cases in which parents are entitled for expenses. It also includes clarification of the extent of parental rights in money of their children, both males and females. The research has found that parents have a right to the money of their children, and that the females have to pay for their parents as much as the males do, and in cases of other the expenses, parental expenses must addedin compliance with God's command to them.
يتناول هذا البحث واحدا من أهم موضوعات نفقات الأقارب في الفقه الإسلامي، الذي يتحمل فيه القريب الموسر النفقة على قريبه المعسر، ويخص بالبيان مسألة نفقة الوالدين وعلى من تجب وكيفية وجوبها ومشتملاتها، وهذا يتضمن بيان مدى حق الوالدين في أموال أولادهم الذكور والإناث على حد سواء. وقد توصل الباحث إلى أن للوالدين حقا واجبا في أموال أولادهم، وأن على البنت النفقة على الوالدين كما هي على الذكر، كما توصل إلى أن نفقة الوالدين إذا تداخلت مع النفقات الأخرى لابد من ضمهم في تلك النفقات ما أمكن، استجابة للأمر الإلهي بالبر بهما والإحسان إليهما.
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الدراسات الفقهية -- قانون الأحوال الشخصية الأردني -- الأردن -- المجتمع الأردني -- نفقة الوالدين -- مستخلصات الأبحاث -- الترجمة